Gait analysis in children with haemophilia: first Italian experience at the Turin Haemophilia Centre. (8th March 2016) - Forneris, E.; Andreacchio, A.; Pollio, B.; Mannucci, C.; Franchini, M.; Mengoli, C.; Pagliarino, M.; Messina, M.
Abstract : Aim: To investigate the functional status in haemophilia patients referred to an Italian paediatric haemophilia centre using gait analysis, verifying any differences between mild, moderate or severe haemophilia at a functional level. Methods: Forty‐two patients (age 4–18) presenting to the Turin Paediatric Haemophilia Centre who could walk independently were included. Therapy included prophylaxis ( n = 21), on‐demand ( n = 17) or immune tolerance induction + inhibitor ( n = 4). Patients performed a test of gait analysis. Temporal, spatial and kinematic parameters were calculated for patient subgroups by disease severity and background treatment, and compared with normal values. Results: Moderate (35.7%) or severe (64.3%) haemophilia patients showed obvious variations from normal across a variety of temporal and spatial gait analysis parameters, including step speed and length, double support, swing phase, load asymmetry, stance phase, swing phase and speed. Kinematic parameters were characterized by frequent foot external rotation with deficient plantar flexion during the stance phase, retropelvic tilt, impaired power generation distally and reduced ground reaction forces. Both Gait Deviation Index and Gait Profile Score values for severe haemophilia patients indicated abnormal gait parameters, which were worst in patients with a history of past or current use of inhibitors and those receiving on‐demand therapy. Conclusion: Functional evaluation identified changes in gait pattern in patients with severe and moderate haemophilia, compared with normal values. Gait analysis may be a useful tool to facilitate early diagnosis of joint damage, prevent haemophilic arthropathy, design a personalized rehabilitative treatment and monitor functional status over time.